Serum proteomic profiling of obese patients: correlation with liver pathology and evolution after bariatric surgery. Issue 6 (10th April 2008) - Trak-Smayra, V; Dargere, D; Noun, R; Albuquerque, M; Yaghi, C; Gannagé-Yared, M-H; Bedossa, P; Paradis, V
Abstract : Objective: Chronic liver diseases, including cirrhosis, may develop in obese patients. Steatosis and non-alcoholic steatohepatitis (NASH) are risk factors for progression to fibrosis. To date, diagnosis of steatosis and NASH relies on liver biopsy. The aim of the study was to identify serum markers of steatosis and NASH in obese patients using SELDI–TOF ProteinChip. Patients: Eighty obese non-alcoholic patient candidates for bariatric surgery and devoid of hepatitis B and C infection were selected. Serum samples were collected before surgery and at 6 months after surgery for 33 of these patients. Wedge liver biopsy was performed at the time of bariatric surgery. Twenty-four serum samples from healthy blood donors served as controls. The protein profiles of each serum were assessed using SELDI–TOF ProteinChip technology and were compared according to liver histological lesions. Results: Twenty-four obese patients (30%) had non-significant liver lesions, 32 (40%) had significant steatosis and 24 (30%) had NASH. Comparison of serum protein profiles according to liver lesions identified three peaks (CM10-7558.4, CM10-7924.2 and Q10-7926.9) the intensity of which significantly increased according to the severity of the liver lesions (steatosis and NASH) and returned to normal after bariatric surgery. None was correlated with either liver function tests or metabolic parameters. Identification using immunoSELDI assay characterised these peaks as the double charged ions of α- and β-haemoglobin subunits. Conclusion: The differential proteomic method demonstrated changes in serum protein profiles in obese patients according to severity of liver lesions. Free haemoglobin subunits may serve as a serum biomarker of the severity of liver damages.